2021
DOI: 10.1094/pdis-01-21-0142-re
|View full text |Cite
|
Sign up to set email alerts
|

Marker-Assisted Development and Evaluation of Monogenic Lines of Rice cv. Kaohsiung 145 Carrying Blast Resistance Genes

Abstract: Rice blast is a serious threat to global rice production. Large-scale and long-term cultivation of rice varieties with a single blast resistance gene usually leads to breakdown of resistance. To effectively control rice blast in Taiwan, marker-assisted backcrossing was conducted to develop monogenic lines carrying different blast resistance genes in the genetic background of an elite japonica rice cultivar, ‘Kaohsiung 145’ (KH145). Eleven International Rice Research Institute (IRRI)-bred blast-resistant lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The ascertainment of the effect of pyramiding on resistance durability would require the long-term monitoring of field resistance for the pyramided lines. However, reports of increased resistance (i.e., fewer lesions) provided by stacking different blast- R genes are available: rice pyramiding of Pi1 + Piz-5 + Pita2 and Pi-1 + Pi-9 + Pi-kh enhanced blast resistance in comparison to a single gene [ 53 , 54 , 55 ]; nine Pi genes were introgressed individually or in combination of two by MABC, and the obtained lines demonstrated that Pigm and Pid3 significantly enhanced resistance during the growth period [ 56 ]; Wu et al [ 57 ] obtained pyramided lines carrying different alleles of the Piz locus ( Pigm , Pi40 , Pi9 , Pi2 , and Piz ) combined with Pi1 , Pi33 , and Pi54 , respectively, and demonstrated that polygene pyramided lines displayed more seedling and panicle blast resistance than monogenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…The ascertainment of the effect of pyramiding on resistance durability would require the long-term monitoring of field resistance for the pyramided lines. However, reports of increased resistance (i.e., fewer lesions) provided by stacking different blast- R genes are available: rice pyramiding of Pi1 + Piz-5 + Pita2 and Pi-1 + Pi-9 + Pi-kh enhanced blast resistance in comparison to a single gene [ 53 , 54 , 55 ]; nine Pi genes were introgressed individually or in combination of two by MABC, and the obtained lines demonstrated that Pigm and Pid3 significantly enhanced resistance during the growth period [ 56 ]; Wu et al [ 57 ] obtained pyramided lines carrying different alleles of the Piz locus ( Pigm , Pi40 , Pi9 , Pi2 , and Piz ) combined with Pi1 , Pi33 , and Pi54 , respectively, and demonstrated that polygene pyramided lines displayed more seedling and panicle blast resistance than monogenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…The lines were found to carry the S5-n gene and exhibit higher seed-setting rates than the control japonica restorer line, indicating the potential for improved fertility in indica-japonica hybrids [32]. Furthermore, the broad-compatibility gene S5-n has been introduced into the maintainer line Zhen5B and the restorer line SIR2622 using molecular marker-assisted breeding, resulting in significant improvements in the fertility of indica-japonica hybrids [36]. Based on the research conducted, it is evident that the introduction of the S5-n molecular marker into restorer lines improves the hybrid vigor of the indica-japonica hybrid F 1 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Liu et al utilized PCR-AccI molecular markers to introduce Wx b into the indica hybrid rice parents Longtefu and Zhenshan97 [11]. Similarly, Chen used molecular marker-assisted selection to obtain a high-quality early indica rice line Ganzaoyou57, which exhibited both high yields and low amylose content [36]. Also, the Wx b gene was inserted into Teqing and Xieyou 57, leading to significant improvements in cooking and eating qualities [11,40].…”
Section: Discussionmentioning
confidence: 99%